Feasibility of a simple drainage system in Cameroonian children after thoracotomy and decortication for empyema thoracis - Bernadette Ngo Nonga; Bonaventure Jemea; Faustin Mouafo Tambo; Nelly Kamgaing; Jean Bahebeck; Maurice A Sosso (Wolters Kluwer Medknow Publications, 2012)
Background: To analyse the outcome of children with empyema thoracis treated by decortication followed by a simple drainage system. Patients and Methods: Retrospective chart review from July 2001 to June 2010 of all cases of children who had a thoracotomy for empyema. We used an endotracheal tube as chest drain and a urinary bag as a collector. Statistical analyses were done using EXCEL and SPSS 9.0. Results: Forty one children underwent thoracotomy and decortication for empyema, there were 23 boys and 18 girls with a sex ratio of 1, 21. The mean age was 2½ years with a minimum of 1 month and a maximum of 15 years of age; 27 children were below two years of age. All the patients have received antibiotic for a long period before surgery. The culture was negative, except in two cases where we found Klebsiella pneumonia and Staphylococcus aureus. In five cases, the empyema was due to Mycobacterium tuberculosis. Three children presented a complication: One child had a persistent purulent drainage for 2 weeks; another one was re-operated upon because of necrotic lung abscess and one child died of sepsis. In most cases, the chest tube was removed between day 4 and day 6 post-operatively. The average length of hospital stay after the surgery was 10 days. Conclusion: Thoracotomy and decortication in children with empyema can be safely done in Cameroon using a simple drainage system with good results compared to those in the literature.